Pathophysiological, Cellular, and Molecular Events of the Vascular System in Anaphylaxis - Nuñez-Borque, Emilio; Fernandez-Bravo, Sergio; Yuste-Montalvo, Alma; Esteban, Vanesa (Frontiers in Immunology, 2022)
Anaphylaxis is a systemic hypersensitivity reaction that can be life-threating. Mechanistically, it results from the immune activation and release of a variety of mediators that give rise to the signs and symptoms of this pathological event. For years, most of the research in anaphylaxis has focused on the contribution of the immune component. However, approaches that shed light on the participation of other cellular and molecular agents are necessary. Among them, the vascular niche receives the various signals that elicit the range of anaphylactic events. Cardiovascular manifestations such as increased vascular permeability, vasodilatation, hypotension, vasoconstriction, and cardiac alterations are crucial in the pathophysiology of anaphylaxis and are highly involved to the development of the most severe cases. Specifically, the endothelium, vascular smooth muscle cells, and their molecular signalling outcomes play an essential role downstream of the immune reaction. Therefore, in this review, we synthesized the vascular changes observed during anaphylaxis as well as its cellular and molecular components. As the risk of anaphylaxis exists both in clinical procedures and in routine life, increasing our knowledge of the vascular physiology and their molecular mechanism will enable us to improve the clinical management and how to treat or prevent anaphylaxis.